Long-term-stable, solution-processable, electrochromic carbon nanotubes/polymer composite for smart supercapacitor with wide working potential window. Issue 39 (26th September 2018) - Ye, Tongtong; Sun, Ying; Zhao, Xuan; Lin, Baoping; Yang, Hong; Zhang, Xueqin; Guo, Lingxiang
Abstract : MWCNT–PBDTC, a solution-processable composite obtained through one-step synthesis, exhibited a wide working potential window, reversible color transition as well as outstanding cycling stability for a smart supercapacitor device. Abstract : Electrochromic supercapacitor (SC) as a multifunctional energy storage device has very important research significance and a broad space for development. The unavoidable challenge for an electrochromic SC is the simultaneous achievement of high energy density, flexibility, and outstanding stability through the use of economically feasible materials and simple manufacturing processes. Despite great efforts in the development of electrochromic SC electrode materials, serious challenges remain for many materials to achieve versatile processability due to their poor solubility. In addition, the voltage window is quite narrow and energy density is relatively low, which limit practical applications. Herein, a novel solution-processable composite material, MWCNT–PBDTC, has been synthesized through direct Williamson reaction between hydroxylated carbon nanotubes (MWCNT-OH) and the conjugated polymer PBDTC-Br with the side chain terminal functionalized with bromo moiety. The electrochromic and electrochemical properties of MWCNT–PBDTC films, obtained by spin-coating, were investigated in detail. Furthermore, an electrochromic symmetrical SC device using MWCNT–PBDTC films as the electrodes was fabricated with PMMA-based solid electrolyte, delivering a high energy density of 174.7 W h kg −1 and a quite wide working potential window of 4.8 V. The cycling stability of the SC was also tested, and the results indicated that the specific capacitance still could retain well over 96% of the initial value after 5000 consecutive charging/discharging cycles. Meanwhile, the SC device exhibited a distinct and reversible color transition from brown (discharged state) to gray (charged state), with a high optical contrast at a wavelength of 465 nm. In short, the novel electrochromic composite could be applied as one of the most promising electrode materials for smart SC devices.